Implementation of Public Complaints to the Ombudsman Regarding Road Infrastructure - Wijayanti, Anisa; Al Meida Putri, Ardhita (Universitas Semarang, 2024)
This research aims to examine the function, role and authority of the Ombudsman representative of Lampung The province accepts public complaints under the Ombudsman Law of the Republic of Indonesia No. 37 of 2008. The thing that underlies this research is the alleged maladministration practices carried out by public service officials of Lampung Province regarding road infrastructure that has not been repaired. This research is a field research with a sociological juridical approach. The results of this study indicate that the Ombudsman of Lampung Province has fulfilled his duties and obligations in accordance with Law No. 37 of 2008 on the Ombudsman of the Republic of Indonesia. Where all incoming complaints have been received, processed and submitted to the authorities in tackling this problem.